Pengaruh Kualitas Pengajaran dan Fasilitas Pelengkap Terhadap Prestasi Mahasiswa Fakultas Dakwah dan Komunikasi UIN Sunan Ampel Surabaya - Millah, Izzatul; Agustin, Dindha Cindy; Al-Adlani, Nur Muhammad Askandar; Ardany, Moh. Haikal; Aditya, Iftikharus Sadat Afif; Afrianto, Dimas (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2024)
This research aims to determine the influence of teaching quality and complementary facilities on student achievement at the Faculty of Da'wah and Communication (FDK) UIN Sunan Ampel Surabaya. Researchers used quantitative methods with non-parametric tests to analyze. Data collection was carried out through questionnaires distributed to 33 FDK UIN Sunan Ampel Surabaya students. This research provides results that can be connected, namely that the quality of teaching partially influences the achievement of students at the Faculty of Da'wah and Communication, UIN Sunan Ampel Surabaya, just as complementary facilities influence the achievement of students at the Faculty of Da'wah and Communication, UIN Sunan Ampel Surabaya. Apart from supporting more effective learning, this research suggests increasing interesting (not boring) lecturer training and providing contemporary facilities so that students at the Faculty of Da'wah and Communication at UIN Sunan Ampel Surabaya are more enthusiastic about participating in teaching and learning activities in class. Meanwhile, simultaneously the quality of teaching and complementary facilities influences student achievement at the Faculty of Da'wah and Communication, UIN Sunan Ampel Surabaya. Therefore, this second factor can make a significant contribution to increasing student achievement.